Research progress on the diagnostic value of fecal calprotectin in colorectal tumors - Jing, Wei; Sun, Jiangshan; Wu, Qingzheng; Zhang, Xiuli (Frontiers in Medicine, 2025)
Fecal Calprotectin (FC), a calcium-binding protein secreted by neutrophils and macrophages and belonging to the S100 protein family, has gained increasing utilization in recent years for the diagnosis and monitoring of intestinal diseases due to its high expression and stability in inflammatory responses. In the field of colorectal tumors, the diagnostic value of FC has gradually emerged. Within colorectal tumors, colorectal cancer (CRC) is an area of significant research focus. Studies have demonstrated significantly elevated FC levels in patients with CRC, a phenomenon potentially linked to chronic inflammation and immune cell infiltration within the tumor microenvironment. FC exhibits notable advantages in colorectal tumor diagnosis, characterized by high sensitivity and moderate specificity. Emerging research has revealed correlations between FC levels and colorectal tumors staging as well as left-sided versus right-sided tumor localization, with elevated FC levels associated with malignant transformation, local inflammation, and advanced tumor stages (T3 and T4). The diagnostic performance of fecal calprotectin (FC) as a non-invasive marker for colorectal tumors has not yet been established. However, due to its association with inflammation, FC holds promise for playing a more significant role in the screening, staging, and localization of colorectal tumors.